Plasma antibody levels (IgG1، IgG2) in periodontitis and control groups - Mosavi M.; Khoshkhonejad AA; Golestan B.; Bahrami N.; Mohamadnia AR; Sadrimanesh R.; Beik zade B. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: A major aspect of the adaptive host response in periodontitis is the antibodies. Several risk and susceptibility factors for periodontitis, including smoking, age and composition of the subgingival microflora, have also been suggested to influence antibody production. The present study was conducted to investigate plasma levels of immunoglobulin (Ig) G antibodies in periodontitis patients of Caucasian Iranian heritage referred to dental faculty, Tehran University of Medical Sciences in relation to disease severity and smoking. "nMaterials and Methods: In this study, 36 patients with severe periodontitis, 39 with moderate periodontitis and 40 controls without periodontal destruction were enrolled. From the total of 80 patients, 21 were diagnosed with aggressive periodontitis and 54 with chronic periodontitis. IgG isotypes were analyzed in plasma samples. "nResults: Patients group in comparison with control group had shown higher level of Immuno globolins. There was no significant difference about the IgG1 level in moderate and seven group and also in chronic and aggressive groups (p<0/001). But the level of IgG2 was shown the significant difference in the all study groups. Smoking was significantly reduced the level of IgG1 and IgG2. "nConclusion: The current study shows that non-smoker periodontitis patients have higher levels of IgG2 than smoker periodontitis patients.